READING GENRE IN TEACHING AND LEARNING ENGLISH - Suaibatul Aslamiah (Al Qalam: Jurnal Ilmiah Keagamaan dan Kemasyarakatan, 2021)
Genre is a type or a kind of reading text commonly found in writing. Reading text is one of the four skills that students must master in English. The various types of the text that students learn can help them to improve their skill. Such as narrative, recount, descriptive text and so on. A part from that, the teacher must be able to choose and analyze the right text so that can help the students develop reading and writing skills. The stages in analyzing text are as follows: register analysis, grammatical rhetorical analysis, interactional analysis and genre analysis. The approach used to teach the genre is an approach emphasizing understanding the text production such as grammar, objectives and language features. The characteristic in the genre based approach are language learning as social activity, explicit teaching and apprenticeship teaching. The pedagogical approaches to teach genre are multiple pedagogical approaches to genre, implicit genre pedagogies, explicit genre pedagogies, and interactive genre pedagogies. Besides that, we can use implicit and explicit method approaches in developing genres. Moreover, the benefits from reading genre analysis are the students can understand the content of the text as a whole, both in term of grammar, factions and so on.